Squamous Versus Adenosquamous Carcinoma in Gall Bladder - Nagar, Neeti; Agrawal, Meetu; Tandon, Megha; Ansar, Junaid (Annals of Pathology and Laboratory Medicine, 2019)
The commonest malignancy developing in gall bladder is an adenocarcinoma. Furthermore, the long-standing presence of gall stones is an inciting event in the development of malignancy. Squamous cell carcinomas have been known in the gall bladder. The squamous origin has been attributed to either of the two theories. It could be either squamous metaplasia in the lining of gall bladder and further malignant transformation or origin of a tumor as adenocarcinoma and its further differentiation towards squamous morphology. We support and demonstrate the latter morphology by means of this case.